Molecular Detection of Some Virulence Genes of Escherichia coli Isolated from UTI Patients in Kirkuk City, Iraq - Ibraheem Salih Aljebory (Journal of Global Pharma Technology, 2016)
This study was conducted at Azadi teaching hospital, Kirkuk hospital and children hospital in Kirkuk city, Iraq. A 150 urine samples were collected from both genders and different ages of patients with suspected urinary tract infections according to the clinical manifestations and symptoms diagnosed by the examining physician then, these samples have been examined by an optical microscopy and bacterial cell detection which was a clear evidence of the existence of pathogenic bacteria. The positive samples were cultured and were kept for the purpose of detecting genes encoding for certain virulence factors by a polymerase chain reaction (PCR) and also to test the antibiotic sensitivity of these isolates. Out of 150 samples, 93 of them were positive pathogenic bacteria. 51 (34%) of which infected with E. coli. 37(72.5%) out of 51 were from patients suffering from Cystitis and the other 14(27.4%) were from patients suffering from Pyelonephritis. The isolates were identified by selective media culture and biochemical test and API 20 E. Our study showed that females 39 isolates (76.4%) were infected more than males 12 isolate (23.5%), especially in the age group between (19-47 years). The DNA was extracted from Escherichia coli isolates by gene aid DNA isolation kit. Polymerase Chain Reaction was used for detecting the virulence genes (fimH, kpsMTII, papC and hlyA ). The result showed that 51 (100%) isolates were carrying fimH gene, 39 (76.4%) isolates were carrying kpsMTII gene, 23 (45%) isolates were carrying papC gene and 13 (25.4%) isolates were carrying hlyA gene.